2007
DOI: 10.1089/jop.2006.0076
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intravitreally Injected Povidone-Iodine onStaphylococcus epidermidisin Rabbit Eyes

Abstract: These results suggest that 400_g of PVP-I can be tolerated intravitreally in rabbit eyes with no noticeable damage over a 14-day period. Results further showed that 100 microg of intravitreally injected PVP-I has no statistically significant effect on rabbit eyes injected intravitreally with 3030 CFU of S. epidermidis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 22 publications
1
36
0
1
Order By: Relevance
“…At this concentration, no retinal toxicity was observed and the electroretinogram remained unaltered. Those results have recently been reconfirmed [11] but the efficacy of PVI in concentrations up to 0.1% proved to be insufficient.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…At this concentration, no retinal toxicity was observed and the electroretinogram remained unaltered. Those results have recently been reconfirmed [11] but the efficacy of PVI in concentrations up to 0.1% proved to be insufficient.…”
Section: Discussionmentioning
confidence: 92%
“…In a recent study, Trost et al [11] suggested that 400 g of PVI can be tolerated intravitreally in rabbit eyes with no noticeable damage over a 14-day period. They also showed that 0.1% given intravitreally had no statistically significant effect on rabbit eyes injected intravitreally with 3,030 CFU of S. epidermidis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) 2.5% 1.5% 0.05 ml 15) 5% 0.1 ml 16) 0.05 0.5% 15) 0.005% 10% 10% 0.1% ( Fig. 2) 17) 2.5 10% (30 120 ) 0.1 1.0% (15 ) 18) 0.05 0.5% 0.1% 0.05 0.5% 0.25% 5, 19) 0.25% (Table 1) Fig.…”
unclassified
“…2) 17) 2.5 10% (30 120 ) 0.1 1.0% (15 ) 18) 0.05 0.5% 0.1% 0.05 0.5% 0.25% 5, 19) 0.25% (Table 1) Fig. 1 Safe and effective concentrations of povidone-iodine from the literature 15,16) . Diagram shows ocular toxic concentrations of povidone-iodine administered by different routes to rabbit eyes (shaded) (1 to 5%), effective bactericidal concentration against bacteria in vitro (0.005 to 10%), safe and highly effective concentrations of povidone-iodine administered to rabbit eyes (0.05 to 0.5%), and 0.25% povidone-iodine concentration used for repeated surface irrigation during surgery (highly effective and non-toxic) The bactericidal effect of povidone-iodine is the highest at a concentration of 0.1%.…”
mentioning
confidence: 99%